2022
DOI: 10.3389/fendo.2022.869780
|View full text |Cite
|
Sign up to set email alerts
|

Axon Guidance Molecules in the Islets of Langerhans

Abstract: The islets of Langerhans, responsible for regulating blood glucose in vertebrates, are clusters of endocrine cells distributed throughout the exocrine pancreas. The spatial architecture of the different cell types within the islets controls cell-cell communication and impacts their ability to collectively regulate glucose. Islets rely on a range of chemotactic and adhesive cues to establish and manage intercellular relationships. Growing evidence indicates that axon guidance molecules such as Slit-Robo, Semaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Interestingly, several of these genes including Kit, Slit1, Sdc3, Map1b, Dab1, Olfm1, Dpysl5 and Flrt1 are involved in morphogenetic processes (Figure 5G). Among them, Slit1 belongs to Slit family of secreted extracellular matrix proteins, which have been recently reported to regulate endocrine cell morphogenesis during mouse endocrinogenesis (34,35). Therefore, this analysis predicts a possible function of Neurod2 in regulating programs that coordinate endocrine cell morphogenesis.…”
Section: Resultsmentioning
confidence: 87%
“…Interestingly, several of these genes including Kit, Slit1, Sdc3, Map1b, Dab1, Olfm1, Dpysl5 and Flrt1 are involved in morphogenetic processes (Figure 5G). Among them, Slit1 belongs to Slit family of secreted extracellular matrix proteins, which have been recently reported to regulate endocrine cell morphogenesis during mouse endocrinogenesis (34,35). Therefore, this analysis predicts a possible function of Neurod2 in regulating programs that coordinate endocrine cell morphogenesis.…”
Section: Resultsmentioning
confidence: 87%
“…For example, recent molecular data obtained from the mouse pancreas showed that epithelial islet cells express Robo receptors. Inactivating Slit-Robo signaling disrupted embryonic islet formation and adult islet architecture 66, 67 , emphasizing an underappreciated role for axon guidance molecules in extra-neuronal contexts. In Drosophila, Robo2 was suggested to be induced by high cell-autonomous JNK signaling and required for the elimination of scrib mutant cells 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Axon guidance plays a vital role in neuronal development and regeneration, regulating the cytoskeleton of growth cones and promoting growth cones to advance, pause, turn, or collapse [40]. In addition, axon guidance affects islet morphology and function by regulating the migration of endocrine progenitor cells, which impacts the level of blood glucose metabolism in the body [41]. Axon guidance molecules interact with receptors to affect the development, maintenance, and resolution of tumors and neuropathic pain through Wnt2 signaling, Eph-ephrin signaling, and the semaphorin-plexin system [42].…”
Section: Discussionmentioning
confidence: 99%